The Influence Of Discipline, Motivation And Work Environment On Employee Performance AT PT. Indonesian Cars Sell (Olx Autos) Solo - Marsalina, Citra Anggun; Hartono, Sri; Maryam, Siti (LPPM Institut Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to determine the effect of discipline, motivation and work environment on the performance of employees at PT. Indonesian Selling Cars (OLX Autos) Solo. This type of research uses descriptive research methods with quantitative analysis. This research was conducted at PT. Indonesian Selling Cars (OLX Autos) which are addressed at HTC Solo Lt. UG Parking Jl. Ir. Soekarno Grogol, Madegondo Hamlet, Sukoharjo Regency, Central Java. This research was conducted by giving questionnaires to all employees of PT. Indonesian Selling Car. The research plan will be carried out for 3 months. The population in this study is 120 employees who work at PT. Indonesian Selling Cars (OLX Autos) Solo. In this study, it was determined that 40% of 120, namely 48, was rounded up to 50 employees. The sampling technique used is incidental sampling technique.The results of this study discipline, motivation and work environment have a simultaneous and significant effect on the performance of employees of PT. Indonesian Selling Cars (OLX Autos) Solo. Based on the t test, the results of discipline, motivation and work environment have a simultaneous and significant effect on the performance of employees of PT. Indonesian Selling Cars (OLX Autos) Solo. Keywords: Discipline, Motivation, Work Environment and Employee Performance.